Ideological conditions of the literature of the Third Reich. Nazi literature and cultural politics - Golaszewski, Marcin; Tomasi-Kapral, Elżbieta (Acta Universitatis Lodziensis. Folia Germanica, 2014)
National Socialism did not only constitute a political doctrine; it was also a kind of worldview that left its mark on German and pan-European culture of the 20th century. The drastic changes that were linked to Hitler’s takeover of power confronted writers and poets with a completely new reality and wholly new conditions of the creative process. Those who could not or would not emigrate had to submit themselves (voluntarily or involuntarily) to the policies and norms decreed by the National Socialists. National Socialism – a conglomerate of different ideologies and ideologemes – perverted certain middle-class values and ultimately aimed towards the total subjugation of all areas of life, culture being among them. The fact that the German middle-class partly shared the values propagated by the Nazis led to an overhasty and unjust assessment of the attitude of writers belonging to the so-called ‘Inner Emigration’. The article at hand outlines the principles of National Socialist cultural politics as well as its relationship to artists. The complicated creative situation of writers and poets in the Third Reich will be shown by representative examples.